2020
DOI: 10.3390/nu12061702
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients in the Prevention of Osteoporosis in Patients with Inflammatory Bowel Diseases

Abstract: The chronic character of inflammatory bowel diseases, such as Crohn’s disease and ulcerative colitis, results in various complications. One of them is osteoporosis, manifested by low bone mineral density, which leads to an increased risk of fractures. The aetiology of low bone mineral density is multifactorial and includes both diet and nutritional status. Calcium and vitamin D are the most often discussed nutrients with regard to bone mineral density. Moreover, vitamins A, K, C, B12; folic acid; calcium; phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 131 publications
1
31
0
Order By: Relevance
“…Therefore, IBD patients should be regularly monitored with regard to malnutrition [ 12 ]. Calcium and vitamin D are the most commonly discussed micronutrients in terms of osteoporosis prevention [ 13 , 14 , 15 , 16 ]; nevertheless, vitamin B12, folic acid, vitamin K, vitamin C, phosphate, magnesium and sodium also play an important role in the prevention of osteoporosis [ 17 ]. According to Owczarek et al, the key nutrients for IBD patients comprise iron, calcium, vitamin D, vitamins B, vitamin A and zinc [ 18 ], but other components of the diet, such as other micronutrients, should be taken into consideration as well.…”
Section: Nutrition In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, IBD patients should be regularly monitored with regard to malnutrition [ 12 ]. Calcium and vitamin D are the most commonly discussed micronutrients in terms of osteoporosis prevention [ 13 , 14 , 15 , 16 ]; nevertheless, vitamin B12, folic acid, vitamin K, vitamin C, phosphate, magnesium and sodium also play an important role in the prevention of osteoporosis [ 17 ]. According to Owczarek et al, the key nutrients for IBD patients comprise iron, calcium, vitamin D, vitamins B, vitamin A and zinc [ 18 ], but other components of the diet, such as other micronutrients, should be taken into consideration as well.…”
Section: Nutrition In Ibdmentioning
confidence: 99%
“…Fortunately, in the recent years, the prevalence of cigarette smoking among IBD patients has reduced in Western countries [ 31 ]. It has been well established that the steroids and biopharmaceuticals used in the IBD therapy also affect bone mineral density [ 17 ]. In fact, Sole reported that infliximab increased BMD of the femoral neck in patients suffering from rheumatoid arthritis [ 32 ].…”
Section: Osteoporosis In Ibdmentioning
confidence: 99%
“…Additionally, infliximab possibly increases the N-terminal telopeptide of type I collagen. However, research regarding the association between the use of infliximab and BMD are contradictory [38].…”
Section: Pharmacological Treatment In Ibdmentioning
confidence: 99%
“…Vitamin C is one of the nutrients which can affect BMD in various mechanisms [61]. On the other hand, nutritional deficiency of other vitamins and minerals, such as calcium and vitamin D, also influence bone mineral density (BMD) [38]. Moreover, the exclusion of other covariates is difficult and many research studies on the association between BMD and vitamin C intake have been observational.…”
Section: Vitamin C and Bone Tissue In Ibd Patientsmentioning
confidence: 99%
“…The most discussed nutrients are vitamin D and calcium. However, sufficient intake of other diet compounds, e.g., protein, magnesium, copper, and zinc, are also essential elements of osteoporosis prevention and treatment [39][40][41].…”
Section: Introductionmentioning
confidence: 99%